FORMULATION AND EVALUATION OF LEMONGRASS (Cymbopogon citratus) ESSENTIAL OIL MOUTH SPRAY FOR THE MANAGEMENT OF GINGIVITIS - Kornialia; Annisa Maika Fadhilah; Yenita Alamsyah; Widya Puspita Sari (Journal of Health and Dental Sciences, 2026)
Gingivitis is a common oral health problem throughout the world. It is an inflammatory disease of the gingival tissues caused mainly by the accumulation of dental plaque. Conventional management often involves synthetic antiseptics such as chlorhexidine; however, prolonged use may cause adverse effects such as tooth staining, taste alteration, and mucosal irritation, highlighting the need for safer, natural-based alternatives. Lemongrass (Cymbopogon citratus) essential oil possesses antibacterial and anti-inflammatory properties, making it a promising ingredient for oral care formulations. This study aimed to formulate and evaluate a mouth spray containing lemongrass essential oil and assess its physical characteristics, stability, and sensory acceptance. The experimental laboratory study used a descriptive approach with two formulations containing 0.25% and 0.5% lemongrass essential oil. Evaluation parameters included organoleptic properties, pH, viscosity, hedonic test, and stability testing during four weeks of storage at room temperature (25 ± 2°C). The results showed that both formulations produced clear, homogeneous liquid preparations. The 0.25% formulation demonstrated a clearer appearance, milder aroma, and fresher taste compared to the 0.5% formulation. The pH values ranged from 5.97 to 6.17, which were within the acceptable range for intraoral use. Viscosity values were 0.983 cPs and 0.993  , respectively, indicating good spray ability. The hedonic test showed a higher preference for panelists in 0.25% formulation. The four-week stability test showed no significant changes in organoleptic properties, pH, or viscosity, indicating that both formulations were physically stable, the 0.25% formulation being better accepted overall. DOI : 10.54052/jhds.v6n1.p79-100